A servidão voluntária e a ascensão da tirania coletiva no Brasil de 2016 ao advento do bolsonarismo - Silva, Gilvania Dias da (2024)
The scope of this research is to study voluntary servitude as a human phenomenon theorized as a political theory in the 16th century by Étienne de La Boétie, addressing it as one of the possible founding elements of social and political relations that structure artificial inequalities between people. From an anthropological philosophical perspective, we investigated the interrelationship between tyranny, as an instrument of subjugation used by the powerful in relation to the weakest, and their adherence as a way of participating in this tyranny by embracing voluntary servitude, as if, instead of losing freedom, they gained servitude. We then analyzed the way in which this tyranny became collectivized, as a way of being for part of the population, mainly because it was part of a social structure that, since the colony, was structured on and under mandonism, a very important political category whose analysis, together with servility, during the process of the formation of Brazil, can help in the etiological understanding of the Brazilian people. The aim was to take a journey through the various phases and main political events that have shaped Brazil and its people, in order to understand at what point, today, there has been such a frank sharing of tyranny to the point of collectivizing it, sustaining this phenomenon in voluntarism to servitude, especially since the 2016 coup d'état, and how and when these two political and social phenomena were captured by what has come to be known as Bolsonarism. We analyzed the main events that characterized and established Bolsonarism as a far-right movement in the national political spectrum, with an internationalist bias and founded on a fascist affection. As well as the methods it has used to co-opt a mass of citizens who, despite the many problems that this political movement has caused and is causing the country, remain loyal and cohesive. At the same time, we analyzed the participation and positions adopted by the portion of Brazilians who oppose Bolsonarism and how the phenomena of tyranny and voluntarism to servitude act on this portion.